Availability of Vending Machines and School Stores in California Schools. (January 2016) - Cisse‐Egbuonye, Nafissatou; Liles, Sandy; Schmitz, Katharine E.; Kassem, Nada; Irvin, Veronica L.; Hovell, Melbourne F.
ABSTRACT: BACKGROUND: This study examined the availability of foods sold in vending machines and school stores in United States public and private schools, and associations of availability with students' food purchases and consumption. METHODS: Descriptive analyses, chi‐square tests, and Spearman product‐moment correlations were conducted on data collected from 521 students aged 8 to 15 years recruited from orthodontic offices in California. RESULTS: Vending machines were more common in private schools than in public schools, whereas school stores were common in both private and public schools. The food items most commonly available in both vending machines and school stores in all schools were predominately foods of minimal nutritional value (FMNV). Participant report of availability of food items in vending machines and/or school stores was significantly correlated with (1) participant purchase of each item from those sources, except for energy drinks, milk, fruits, and vegetables; and (2) participants' friends' consumption of items at lunch, for 2 categories of FMNV (candy, cookies, or cake; soda or sports drinks). CONCLUSIONS: Despite the Child Nutrition and Women, Infants, and Children (WIC) Reauthorization Act of 2004, FMNV were still available in schools, and may be contributing to unhealthy dietary choices and ultimately to health risks.